GENDER MAINSTREAMING POLICY IN ISLAMIC EDUCATION IN INDONESIA: STUDENTS’ PERCEPTIONS ON GENDER ROLES IN ISLAMIC PRIMARY SCHOOL - Sitti Azisah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2009)
The Indonesian government has made a strong commitment to eliminate gender discrimination. To achieve greater gender equality and equity, President Abdurrahman Wahid issued the Presidential Instruction Number 9 Year 2000 to promote gender mainstreaming with the objective of achieving gender equality and equity in all sectors of life. This paper investigates gender perspec-tives of the students in three Islamic Primary schools: one state school and two private schools in South Sulawesi, Indonesia. The data were gathered by using a number of techniques: group interviews, student drawings, listing famous people and selecting favorite person from their lists of famous people. Three main points emerged from the study: 1) the majority of students had gender-neutral views on sports/games, employment and a range of other social activities; 2) persistent gender stereotyping of some roles by students; and 3) the students from the three schools had divergent views on gender roles and gender identities.